Location optimization for vaccination centers of the andean region in Peru - Lima Quiroz, Mariela Mercedes (2023)
The COVID-19 pandemic has taken a devastating economic, social and health toll. Although vaccines have been developed to combat it, access to them was not equitable for all, especially in developing countries. Peru faces additional challenges: poor health and road infrastructure, a tight health budget and shortage of healthcare personnel. The objective of this study is to define the optimal location for vaccination centers in the most adverse regions of Peru. A mathematical model for the optimization of the location is presented taking as a reference the Set Covering, Maximal Covering and P- Median models. Coverage, location costs and travel distance were prioritized. The sample used was the district of Kimbiri in Cusco. Of the seventy rural communities and nine health centers available, 55 and 7 were included, respectively. One vaccination center was assigned per rural community. The resulting metrics were 93.6% coverage, 77.78% resource utilization and an average travel distance of 929.25 meters. This model can be used to optimize immunization processes in developing countries.